Modern Conflicts Features in Latin America. The Role of the OAS in the Settlement of the Falklands Conflict - Y. I. Strashko (Vestnik MGIMO-Universiteta, 2015)
The article is an attempt to give careful examination to the issue of intergovernmental conflicts and the OAS's (The Organization of American states) activity on ensuring security in Latin America in particular. The article's focus on last decades is not accidental. The 30-40th of the XX century were marked by major military conflicts in South America that, however, were sidelined after the Second World War. Created on the verge of the Cold war the OAS was considered by the States as a barrier to the spread of communist threat in the Western Hemisphere and in such a capacity the organization went on up to detente policy implementation. All the time the OAS had to challenge different crises. By the time the bipolar world order seized to exist the OAS had had another mission. It was no longer the provision of international security but the local conflicts management including long-standing territorial disputes. The difference in approach to Organization's role and status between the US and Latin American states became distinct in the same period. The former persist in protection of freedoms and the Western way of life against global threats such as international terrorism (especially after 9/11), drug trafficking, gunrunning, money laundering and others crimes (especially those involving violence). The latter are trying to engage the OAS potential to protect their own national and regional interests while becoming integrated into a new global economic and political relations system. Trying to meet the modern challenges the OAS not only creates new bodies, but also makes significant changes in its statutory documents, which unlike the UN makes it more responsive to internal crises. Besides there is a distinct tendency of the Organization's becoming more independent from the US.